2017
DOI: 10.3892/or.2017.5585
|View full text |Cite|
|
Sign up to set email alerts
|

RON and c-Met facilitate metastasis through the ERK signaling pathway in prostate cancer cells

Abstract: Prostate cancer (PCa) is a metastatic malignant cancer driven by complex pathological mechanisms and characterized by poor long-term prognosis. Metastasis is the main cause of death of PCa patients, yet the molecular mechanisms of this process are poorly understood. In the present study, positive co-expression of RON and c-Met was observed in human clinical PCa tissues (biopsy material), as detected by immunohistochemical staining and quantitative real-time PCR. We investigated this further in PCa cells, demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…The concentrations of serum HGF measured by Nagakawa et al turned out to be higher than in our study, but the relationship remains similar. The study by Yin et al shows increased expression of c-Met , the HGF receptor in prostate cancer cells in vitro, in metastatic-dependent manner [ 76 ]. It allows to use HGF as a potential indirect prostate cancer biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of serum HGF measured by Nagakawa et al turned out to be higher than in our study, but the relationship remains similar. The study by Yin et al shows increased expression of c-Met , the HGF receptor in prostate cancer cells in vitro, in metastatic-dependent manner [ 76 ]. It allows to use HGF as a potential indirect prostate cancer biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that IBC inhibited the invasion of Tca8113 cells by downregulating MMP-2 and MMP-9 protein expression. Previous studies have demonstrated that abnormal activation of ERK/p-ERK is able to activate a series of cytoplasmic proteins to promote the invasion and metastasis of cancer cells ( 25 , 26 ). In addition, the Akt signaling pathway also served a role in the expression of MMP-2 and MMP-9 proteins ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…SEMA is the site where HGF binds directly to c-Met, and PSI can stabilize this interaction. Ser-975 and Tyr-1003 sites at the juxtamembrane domain play an important role in the negative regulation of c-Met [ 14 , 22 , 23 ]. When HGF binds c-Met, Tyr-1234 and Tyr-1235 in the intracellular tyrosine kinase domain undergo autophosphorylation, which results in autophosphorylation of Tyr-1349 and Tyr-1356 in the C-terminal docking site.…”
Section: Structures Of C-met and Hgfmentioning
confidence: 99%
“…The most common grade 3 and higher toxic adverse reactions were mainly high blood pressure, diarrhea, nausea, and fatigue. Yin et al [ 22 ] also demonstrated that foretinib inhibits prostate cancer (PCa) metastasis by targeting c-Met.…”
Section: Current Clinical Trials Targeting C-metmentioning
confidence: 99%